2010
DOI: 10.1146/annurev-fluid-121108-145504
|View full text |Cite
|
Sign up to set email alerts
|

Friction Drag Reduction of External Flows with Bubble and Gas Injection

Abstract: The lubrication of external liquid flow with a bubbly mixture or gas layer has been the goal of engineers for many years, and this article presents the underlying principles and recent advances of this technology. It reviews the use of partial and supercavities for drag reduction of axisymmetric objects moving within a liquid. Partial cavity flows can also be used to reduce the friction drag on the nominally two-dimensional portions of a horizontal surface, and the basic flow features of two-dimensional caviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
263
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(266 citation statements)
references
References 83 publications
1
263
0
2
Order By: Relevance
“…Drag reduction for turbulent flows has also been reported [8]. SHPo surfaces are considered a superior alternative to the existing bubble injection method [10] for drag reduction, because the stable gas upon the surfaces makes the SHPo method passive (i.e., energy efficient) and simple (i.e., easy implementation). Moreover, it has been shown that the minimized solid-liquid contact on SHPo surfaces can resist surface fouling [11].…”
Section: University Of California Los Angeles (Ucla) California 900mentioning
confidence: 99%
“…Drag reduction for turbulent flows has also been reported [8]. SHPo surfaces are considered a superior alternative to the existing bubble injection method [10] for drag reduction, because the stable gas upon the surfaces makes the SHPo method passive (i.e., energy efficient) and simple (i.e., easy implementation). Moreover, it has been shown that the minimized solid-liquid contact on SHPo surfaces can resist surface fouling [11].…”
Section: University Of California Los Angeles (Ucla) California 900mentioning
confidence: 99%
“…However, despite several attempts in this field, the physical mechanisms implied into the bubbly drag reduction are to the best of our knowledge, not completely understood 1 . Consequently, it is still non straightforward to extrapolate results obtained for small scale models to large scale ship's hull model.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the drag of marine vehicles via gas lubrication has long been practiced by injecting gas bubbles or creating a cavitation gas pocket (Ceccio 2010) and reached a significant drag reduction (~ 95%) at a high Reynolds number (Re x ~ 10 7 ) flow (Lay et al 2010). Since the gas film (or bubbles) does not stay on the solid surface by nature, however, these methods should continue supplying the gas with additional energy, overshadowing the benefit of drag reduction and limiting applications.…”
Section: Introductionmentioning
confidence: 99%